Corrigendum: Vascular Access Management After Kidney Transplantation Position Paper on Behalf of the Vascular Access Society and the European Kidney Transplant Association - Akin, Barış; Jemcov, Tamara K; Cucchiari, David; Malik, Jan; Pettigrew, Gavin J; Lundström, Ulrika Hahn; Zaza, Gianluigi; Rotmans, Joris I (Transplant international, 2025)
[This corrects the article DOI: 10.3389/ti.2025.14712.].
Keywords: kidney failure; AVF flow reduction; hemodialysis; ligation of arteriovenous fistula; kidney transplantation